Latest progress on the influencing factors affecting the formation of TiO2 nanotubes (TNTS) in electrochemical anodization- A minireview - Hossen, Md. Arif; Yaacof, Nurashikin; Abd Aziz, Azrina; Lihua, Wu (Zibeline International Publishing, 2023)
TiO2 nanotubes (TNTs) have drawn special attention for their wide range of applications in a variety of fields. In comparison to other TiO2 nanostructures, it is attracted much due to its high surface area and low fabrication cost. By using the electrochemical anodization approach, highly ordered TNT arrays can be produced with minimum cost compared to other synthesized methods. The nanotubes of the desired diameter, length and wall thickness can be tailored by adjusting anodization parameters. Here in this article, the effects of anodization parameters including type of electrolytes, electrolyte concentration, pH, temperature, aging, anodization voltage, time and type of electrodes on tube formation, tube diameters, length, thickness, organization, and formation mechanisms are reviewed. The collection methods of asproduced TNTs from Ti substrate also summarized in this review. Finally, the article concludes by outlining potential future research scope and challenges.